STUDENTS’ NEEDS OF ENGLISH SPEAKING MATERIALS IN TOURISM VOCATIONAL SCHOOL IN PADANG - Yunus, Yuliawati (RC-INSTITUT, 2019)
The aims of this study is to find out the students? needs in speaking materials related to necessities, lacks, and wants. The subjects of this study were tenth grade students of hotel accommodation major at tourism vocational school in Padang. The instruments used in this study were questionnaires. There are only fifth questions in the questionnaires related to necessities, lacks and wants. The result of questionnaires showed that first, topic needed in learning English speaking is topic related to daily life, the percentage is 16.4%, second,  after graduate, the students will use English speaking skill in workplace, the percentage is 42.1%, third, main difficulties when learning English speaking is vocabularies, the percentage is 80%, fourth, narrator that the students want for listening activities is adult, the percentage is 60%, last, accent that the students want for listening activities is American, the percentage is about 70%. Considering the needs, for next study the researcher will speaking materials which for tourism vocational students.